Recovery of the patient with scapulo-humeral polyarthritis by kinetic means - Benedek Florian (Editura Univeristatii "Stefan cel Mare" din Suceava, 2024)
The research objectives are found below and refer to the examination, testing, application and recording of data. The study was carried out over a period of 3 months, where the patient, through the kinetic and akinetic means and methods used, led to the recording of considerable results that are recorded in the work. The results were carefully analyzed and compared with those from the initial testing to see the patient's progress. This condition has recently become a real problem among people, in the vast majority of people of the second age are the most affected by this syndrome. The muscles are not sufficiently warmed up and prepared for the efforts we perform every day, the lack of training and physical activity is a real problem because most people subject their joints to certain shocks during movements, and the dysfunctionality of the shoulder and the pain present during movement and during the night it is not pleasant at all.[4]